2000
DOI: 10.1097/00004714-200008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Versus Oral Administration of Amitriptyline in Patients With Major Depression

Abstract: Antidepressants can be administered by different routes. Advantages for either the oral or the intravenous administration have been suggested from pharmacokinetic as well as from clinical points of view. Controlled comparison studies of the two routes do not provide unequivocal recommendations. In this investigation, amitriptyline was studied over a 4-week period consisting of a 2-week, double-blind/double-dummy phase with either oral (150 mg/day), high-dose intravenous (150 mg/day), or medium-dose intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Clinical findings have been replicated and extended to other antimuscarinics and treatment populations (Howland, 2009;Dagyt_ e et al, 2011;Janowsky, 2011;Drevets et al, 2013;Jaffe et al, 2013). It is noteworthy that amitriptyline, a tricyclic antidepressant with greater efficacy than SSRIs (Anderson, 1998;Deisenhammer et al, 2000), has one of the richest of antimuscarinic profiles (Rathbun and Slater, 1963). Given the reenergizing of both the cholinergic hypothesis of MDD and the pressing need for improved antidepressant agents, we undertook the present series of studies.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical findings have been replicated and extended to other antimuscarinics and treatment populations (Howland, 2009;Dagyt_ e et al, 2011;Janowsky, 2011;Drevets et al, 2013;Jaffe et al, 2013). It is noteworthy that amitriptyline, a tricyclic antidepressant with greater efficacy than SSRIs (Anderson, 1998;Deisenhammer et al, 2000), has one of the richest of antimuscarinic profiles (Rathbun and Slater, 1963). Given the reenergizing of both the cholinergic hypothesis of MDD and the pressing need for improved antidepressant agents, we undertook the present series of studies.…”
Section: Discussionmentioning
confidence: 95%
“…The difference in muscarinic receptor affinity across TCAs may explain why amitriptyline was the only antidepressant drug that proved more effective than more selective agents (eg, selective serotonin reuptake inhibitors) in inpatients with MDD. 46,54,57 Nevertheless, in clinical practice, the amitriptyline dose is gradually titrated upward, so potentially rapid responses to full therapeutic amitriptyline doses would not have been detected.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…One shortcoming of conventional antidepressant treatments is that the several-week delay needed to achieve clinically meaningful improvement prolongs patients' vulnerability to suicide and disability. Treatments that produce antidepressant responses within 1 week-electroconvulsive therapy, high-dose TCA drug administration, total sleep deprivation, and ketamine use [44][45][46][47][48] -have not proved amenable to widespread clinical application because of their adverse effects or the transient nature of their therapeutic benefits. In contrast, the absence of serious adverse effects encountered in this study suggests that scopolamine may provide a relatively safe and well-tolerated intervention for achieving rapid antidepressant responses.…”
Section: Commentmentioning
confidence: 99%
“…In the case of maprotiline [Kissling et al, 1985], oral administration was found to be more advantageous. For amitryptiline [Deisenhammer et al, 2000], no significant differences were reported between oral, i.v., and high-dose i.v. administration despite a trend in favor of high-dose i.v.…”
Section: Efficacymentioning
confidence: 86%